2015
DOI: 10.1007/s00167-015-3641-5
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic proximal versus open subpectoral biceps tenodesis with arthroscopic repair of small- or medium-sized rotator cuff tears

Abstract: III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
50
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(53 citation statements)
references
References 32 publications
(37 reference statements)
1
50
2
Order By: Relevance
“…Arthroscopic proximal fixation and small incision-assisted distal fixation are common. In recent years, there have also been clinical studies on the comparison of the efficacy between distal and proximal fixation of the LHBT (15,16,(54)(55)(56)(57)(58), all of which suggested that the two methods have a good clinical efficacy, high patient satisfaction and few complications; no significant differences were observed in functional recovery, pain improvement and complications between the two methods. However, in the study by Duchman et al (15), a significant difference was observed in the shoulder flexion function between the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…Arthroscopic proximal fixation and small incision-assisted distal fixation are common. In recent years, there have also been clinical studies on the comparison of the efficacy between distal and proximal fixation of the LHBT (15,16,(54)(55)(56)(57)(58), all of which suggested that the two methods have a good clinical efficacy, high patient satisfaction and few complications; no significant differences were observed in functional recovery, pain improvement and complications between the two methods. However, in the study by Duchman et al (15), a significant difference was observed in the shoulder flexion function between the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…We also assessed trends in concomitant procedures associated with rotator cuff repair surgery in Medicare patients, as 1 study suggested that the rates of these procedures have been increasing 31 despite there currently being a lack of evidence supporting their use. 1 , 17 , 22 , 29 , 33 …”
mentioning
confidence: 99%
“…There was a significant improvement (p<0.001) at follow-up for UCLA and Constant score, VAS for pain at rest and during motion, similarly in both groups, whereas ROM evaluation did not show significant improvement at the latest follow-up. Yi et al 23 reviewed 66 patients who underwent arthroscopic RC repair with arthroscopic proximal biceps tenodesis through a bioabsorbable interference screw (34 cases) or with open subpectoral tenodesis (32 cases). Within 3 months postoperatively, the VAS score significantly improved in the open subpectoral tenodesis group compared with the arthroscopic proximal tenodesis group (p<0.05), but no significant difference was found in the VAS score between the two groups after 6 months.…”
Section: Resultsmentioning
confidence: 99%
“…In the study by Jeong et al ,19 a comparable improvement in Constant and UCLA scores was found for both treatment groups, and slightly better flexion of the shoulder was achieved in the patients managed arthroscopically. Yi et al 23 found a significant difference in VAS for pain at short-term follow-up (2 weeks and 3 months), whereas the difference at 6 months became not significant, both for ASES and Constant scores. Given the lack of significant data on the topic, from a clinical point of view and from a case-management perspective, a few consideration must be taken into account.…”
Section: Discussionmentioning
confidence: 96%